From glanders to Hendra virus: 125 years of equine infectious diseases. (31st August 2013) - Slater, Josh
Abstract : Josh Slater looks back at the past 125 years of developments in equine infectious disease, including landmark discoveries in microbiology and genomics, and considers what the future may hold